A regional head election’s political corruption and new styles of clientelism - Muhammad Habibi (Masyarakat, Kebudayaan dan Politik, 2021)
Intense competition in the regional head election (Pilkada) has implications for the increasing costs that candidates have to prepare to win the competition. The high cost in the regional head election makes many regional heads, when elected, commit political corruption and practices that are more adapted to the situation, namely the new styles of clientelism. This study aims to determine the shift in the relationship between political corruption and clientelism and to see new forms of clientelism. The approach used in this research was a literature study. Documents were selected using an application from the Publish or Perish database. The results of this study indicate that first, the power of money in politics in Indonesia creates a significant dependence on economic power, which influences a high level of political corruption. Second, there are two new styles of clientelism, including buying and selling votes and patronage in the bureaucracy. This paper concludes that the various modes of political corruption and new styles of clientelism that occur underline political vulnerabilities at the local level due to the broad elaboration of regional authority discretion.